(untitled) (Revista de Letras Norte@mentos, 2011)
Once the contemporaneity of the 1969 novel Slaughterhouse-Five by American writer Kurt Vonnegut is established, the text outlines the narrative strategies, the stylistic preferences and the peculiar techniques of wording that, together, build up the author’s distinctive individual style nowadays so frequently associated to him. The study also highlights his incomparable sense of humor, his sagacity and satiric wit, as the foremost elements of creation that provide unique hue to his stories. Finally, metatextual instances are selected for investigation as well as his atypical fictional technique referred here as space-temporal dislocation.